Efficient mapping algorithms for a class of hierarchical systems - Ziavras, S.G. (IEEE transactions on parallel and distributed systems, 1993)
Proposes techniques for mapping application algorithms onto a class of hierarchically structured parallel computing systems. Multiprocessors of this type are capable of efficiently solving a variety of scientific problems because they can efficiently implement both local and global operations for data in a two-dimensional array format. Among the set of candidate application domains, low-level and intermediate-level image processing and computer vision (IPCV) are characterized by high-performance requirements. Emphasis is given to IPCV algorithms. The importance of the mapping techniques stems from the fact that the current technology cannot be used to build cost-effective and efficient systems composed of very large numbers of processors, so the performance of various systems of lower cost should be investigated. Both analytical and simulation results prove the effectiveness and efficiency of the proposed mapping techniques.< >